2009
DOI: 10.1002/bdm.630
|View full text |Cite
|
Sign up to set email alerts
|

Better safe than sorry: Precautionary reasoning and implied dominance in risky decisions

Abstract: In four studies, student and nonstudent participants evaluated the possible outcomes of binary decisions involving health, safety, and environmental risks (e.g., whether to issue a dam-failure evacuation order). Many participants indicated that false positives (e.g., evacuation, but no dam failure) were better than true negatives (e.g., no evacuation and no dam failure), thereby implying that an incorrect decision was better than a correct one, and that the more protective action dominated the less protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…This well-replicated finding contradicts most descriptive and normative theories of choice (e.g., prospect theory, regret theory, expected utility theory, multiattribute utility theory), which assume that the evaluation of information affects the evaluation of alternatives, but not vice versa (DeKay et al, 2009a(DeKay et al, , 2009b(DeKay et al, , 2011Glöckner et al, 2010;Holyoak & Simon, 1999;Russo & Yong, 2011;Simon, Snow, & Read, 2004). In contrast, one descriptive theory that does not assume unidirectionality is parallel constraint satisfaction (PCS), a coherence-maximizing connectionist model that incorporates bidirectional links between the choice options and the input information (Glöckner et al, 2010;Holyoak & Simon, 1999;Simon, Snow, & Read, 2004).…”
mentioning
confidence: 55%
“…This well-replicated finding contradicts most descriptive and normative theories of choice (e.g., prospect theory, regret theory, expected utility theory, multiattribute utility theory), which assume that the evaluation of information affects the evaluation of alternatives, but not vice versa (DeKay et al, 2009a(DeKay et al, , 2009b(DeKay et al, , 2011Glöckner et al, 2010;Holyoak & Simon, 1999;Russo & Yong, 2011;Simon, Snow, & Read, 2004). In contrast, one descriptive theory that does not assume unidirectionality is parallel constraint satisfaction (PCS), a coherence-maximizing connectionist model that incorporates bidirectional links between the choice options and the input information (Glöckner et al, 2010;Holyoak & Simon, 1999;Simon, Snow, & Read, 2004).…”
mentioning
confidence: 55%
“…Other work shows that holding consequences constant, people appear to prefer options that involve non‐action over action, or decisions that preserve rather than change the status quo (Baron, ). The outcomes of a risky decision seems to be partly evaluated on the basis of the decisions that might lead to them, which is in conflict with consequentialist decision models; the decision itself might be seen as an attribute of possible outcomes (Dekay, Patino‐Echeverri, & Fischbeck, ).…”
Section: Deciding and Emotionsmentioning
confidence: 99%
“…This systematic revaluation of the evidence is called a coherence shift (Holyoak & Simon, ) or coherence effect (Simon, ). Coherence shifts have been demonstrated in a wide variety of tasks (e.g., Brownstein, Read, & Simon, ; DeKay, Patino‐Echeverri, & Fischbeck, , ; Glöckner, Betsch, & Schindler, ; Russo et al, ; Russo et al, ; Simon, Krawczyk, Bleicher, & Holyoak, ; Simon, Krawczyk, & Holyoak, ) and particularly for legal judgments (Carlson & Russo, ; Glöckner & Engel, ; Holyoak & Simon, ; Simon, ). It has, however, been shown that coherence effects are transient and disappear after some time (Simon, Krawczyk, et al, ).…”
Section: Introductionmentioning
confidence: 99%